Effects of Prescription Drug Reduction on Quality of Life in Community-Dwelling Patients with Dementia - Mikio Sakakibara; Ataru Igarashi; Yoshimasa Takase; Hiroyuki Kamei; Toshitaka Nabeshima (Frontiers Media S.A., 2015)
Purpose: Due to the use of multiple drugs and prevalence of diminished cognitive function, community-dwelling elderly individuals are more likely to have drug-related issues. We examined changes in quality of life (QOL) and activities of daily living (ADL) 3 months and 6 months after reducing drug use of dementia patients who had newly begun community-dwelling care.  Methods: Prescription drug use was reduced in the intervention group, whereas the non-intervention group continued their regimen or began using additional drugs. QOL and ADL were assessed with the Japanese version of the EQ-5D and the Barthel Index, respectively.  Results: Subjects were 32 individuals aged ≥65 years who had begun community-dwelling between March and July 2014 and had received approval for long-term care insurance. On average, the intervention group (n = 19) stopped using 2.6 prescription drugs. After 6 months, the differences in the QOL and ADL scores in the intervention group were -0.03 ± 0.29 and 6.32 ± 18.6, respectively, while the differences in the QOL and ADL scores in the non-intervention group (n = 13) were -0.13 ± 0.29 and -2.69 ± 23.7, respectively. In the intervention group, ADL scores were significantly increased by 14.0 ± 11.1 6 months after reduced benzodiazepine use.  Conclusions: QOL was maintained with reduced drug use, while ADL score was slightly increased. In addition, the reduction of benzodiazepine use significantly increased ADL. In order to reduce polypharmacy among community-dwelling elderly patients, it is necessary to create an opportunity for pharmacists to re-examine their prescriptions   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.